2003
DOI: 10.1053/gast.2003.50155
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of symptom pattern, psychosocial factors, and pathophysiological mechanisms in severe functional dyspepsia

Abstract: In a tertiary care population, functional dyspepsia is a heterogeneous condition characterized by 4 major dimensions differentially associated with psychopathological and physiopathological mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
113
2
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 32 publications
(32 reference statements)
7
113
2
5
Order By: Relevance
“…In this study, early satiety symptom was associated with delayed gastric emptying and days of sickness leave. By contrast, epigastric pain and epigastric burning symptoms were correlated with gastric hypersensitivity and psychopathology or somatization (Fischler et al, 2003). Some gut hormones are known to be the cause of delayed gastric emptying e.g.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, early satiety symptom was associated with delayed gastric emptying and days of sickness leave. By contrast, epigastric pain and epigastric burning symptoms were correlated with gastric hypersensitivity and psychopathology or somatization (Fischler et al, 2003). Some gut hormones are known to be the cause of delayed gastric emptying e.g.…”
Section: Discussionmentioning
confidence: 93%
“…The FD symptom subtypes were developed as a result of factor analysis studies, [29][30][31] as well as reports that up to 80% of patients reported symptom aggravation after ingestion of a meal, 32 and the observation that response to therapy differed by symptom subgroup in clinical trials of proton pump inhibitors in FD. 33 Novel therapies for dyspepsia continue to be developed and tested based on these subtypes.…”
Section: Prevalence Of Erosive Esophagitis According To Fd Definitionmentioning
confidence: 99%
“…The pathophysiology of FD is poorly understood. Recent studies showed that FD is a heterogeneous disorder wherein different pathophysiologic disturbances underlie different symptoms (11). Delayed gastric emptying and abnormalities of gastrointestinal motility have been observed in a considerable proportion of patients with FD (5).…”
Section: Discussionmentioning
confidence: 99%